1999
DOI: 10.1890/0012-9658(1999)080[2338:wcdiit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

What Constrains Daily Intake in Thomson’s Gazelles?

Abstract: We tested whether cropping or digestion by Thomson’s gazelles (Gazella thomsoni) constrains daily energy intake under sward conditions normally encountered during the growing season. Distinguishing between these alternatives is important in understanding grass–grazer interactions and modeling grazer energetics. Grazing trials on artificial swards showed that gazelles had a monotonically saturating functional response, but that relationships between grazing rate and forage density changed with grass height. Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 51 publications
3
97
0
Order By: Relevance
“…According to the forage maturation hypothesis (FMH; Fryxell, 1991), the daily intake of digestible nutrients is highest on swards of intermediate height because of the inverse relationship between the abundance and the quality of plant tissues. This has been confirmed in ruminants by estimating daily rates of energy gain in relation to grass biomass (Wilmshurst et al, 1999a and1999b;Drescher et al, 2006), and many studies demonstrated that animals select for patches with intermediate biomass (Wilmshurst et al, 1995(Wilmshurst et al, , 1999a(Wilmshurst et al, and 1999b. In our study, the effect of grass height on feeding site selection by horses was strongest in the H pasture where there was more variation in height; the animals selected the shortest heights which is a typical pattern for horses in temperate grasslands (see references in Mé nard et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…According to the forage maturation hypothesis (FMH; Fryxell, 1991), the daily intake of digestible nutrients is highest on swards of intermediate height because of the inverse relationship between the abundance and the quality of plant tissues. This has been confirmed in ruminants by estimating daily rates of energy gain in relation to grass biomass (Wilmshurst et al, 1999a and1999b;Drescher et al, 2006), and many studies demonstrated that animals select for patches with intermediate biomass (Wilmshurst et al, 1995(Wilmshurst et al, , 1999a(Wilmshurst et al, and 1999b. In our study, the effect of grass height on feeding site selection by horses was strongest in the H pasture where there was more variation in height; the animals selected the shortest heights which is a typical pattern for horses in temperate grasslands (see references in Mé nard et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Shipley et al (1999) successfully predicted browse selection from considerations of diet quality, and it has been noted that browsers respond to both food quality and availability by eating a higher-quality diet and taking less from each plant at high food densities (Vivås & Saether 1987;Andersen & Saether 1992;Shipley & Spalinger 1995). This suggests that diet optimization under digestive constraints may be the fundamental process in browser foraging, as it appears to be in other mammalian herbivores (Belovsky 1978;Fryxell 1991;Doucet & Fryxell 1993;Wilmshurst, Fryxell & Colucci 1999). As Fortin, Fryxell & Pilote (2002) make clear, the important question is one of time-scale.…”
Section:       mentioning
confidence: 95%
“…The present results for the smallest grazer, Thomson's gazelle, conform to previous study in the area (Wilsey 1996). Thomson's gazelles are known to make more utilization of areas with sward of low to intermediate biomass (Wilmshurst et al 1999;Fryxell et al 2004). In the Serengeti, burnt areas carry low phytomass and have a relatively short sward compared to vegetation in non-burnt patches ), a situation which favours Thomson's gazelle requirement.…”
Section: Patch Contrastsmentioning
confidence: 99%